Plasmonic Metasurfaces for Switchable Photonic Spin–Orbit Interactions Based on Phase Change Materials. Issue 10 (28th August 2018) - Zhang, Ming; Pu, Mingbo; Zhang, Fei; Guo, Yinghui; He, Qiong; Ma, Xiaoliang; Huang, Yijia; Li, Xiong; Yu, Honglin; Luo, Xiangang
Abstract: Metasurfaces with intense spin–orbit interactions (SOIs) offer an appealing platform for manipulation of polarization and wavefront. Reconfigurable beam manipulation based on switchable SOIs is highly desired in many occasions, but it remains a great challenge since most metasurfaces lack the flexibility and the optical performance is fixed once fabricated. Here, switchable SOIs are demonstrated numerically and experimentally via the combination of plasmonic metasurfaces with phase change materials (PCMs). As a proof‐of‐concept, three metadevices possessing switchable SOIs are fabricated and investigated, which enable spin Hall effect, vortex beam generation, and holography when the PCM is in the amorphous state (corresponding to the "ON" state of SOI). When the PCM changes into the crystalline state (corresponding to the "OFF" state of SOI), these phenomena disappear. Experimental measurements show that a high polarization conversion contrast between "ON" and "OFF" states is obtained within a broadband wavelength range from 8.5 to 10.5 µm. The switchable photonic SOIs proposed here may provide a promising route to design reconfigurable devices for applications such as beam steering, dynamic holographic display, and encrypted optical communications. Abstract : Metadevices with switchable spin‐orbit interactions offer an appealing platform for dynamic and reconfigurable beam manipulation which is one important developing trend in photonic devices. Here, such devices are experimentally demonstrated via the combination of plasmonic metasurfaces and phase‐change materials. It is believed that this work made a major step forward to achieve on‐demand beam manipulation.